Can Hospital-Based Doctors Change Their Working Hours? Evidence from Australia - Norman, Richard; Hall, J. (Blackwell Publishing, 2014)
Background and Aims: To explore factors predicting hospital-based doctors’ desire towork less, and then their success in making that change. Methods: Consecutive waves of an Australian longitudinal survey of doctors (Medicine in Australia – Balancing Employment and Life). There were 6285 and 6337 hospital-based completers in the two waves, consisting of specialists, hospital-basednon-specialists and specialist registrars.Results: Forty-eight per cent stated a preference to reduce hours. Predictive characteristicswere being female and working more than 40 h/week (both P <0.01). An inverted U-shape relationship was observed for age, with younger and older doctors less likely to state the preference. Factors associated with not wanting to reduce working hours were being in excellent health and being satisfied with work (both P <0.01). Of those who wanted to reduce working hours, only 32% successfully managed to do so in the subsequent year (defined by a reduction of at least 5 h/week). Predictors of successfully reducing hours were being older, female and working more than 40 h/week (all P < 0.01).Conclusion: Several factors predict the desire of hospital-based doctors to reduce hours and then their subsequent success in doing so. Designing policies that seek to reduce attrition may alleviate some of the ongoing pressures in the Australian hospital system.